2010
DOI: 10.1155/2010/263827
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Panniculitis and Insect Bite‐Like Eruption in a Patient with Chronic Lymphocytic Leukaemia: A Spectrum of the Same Entity

Abstract: Background. Eosinophilic dermatosis of hematologic disorders is a reactive process that may cause a variety of clinical manifestations. Methods. We report a patient who had outbreaks of skin lesions since the onset of chronic lymphocytic leukaemia. Results. The cutaneous eruptions began as eosinophilic panniculitis and after changed to insect bite-like lesions. Conclusion. We think that eosinophilic panniculitis and insect bite-like lesions may be part of the spectrum of the same entity in patients with hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
3
24
0
1
Order By: Relevance
“…The characteristic histological feature is the presence of an eosinophil‐rich, perivascular and periadnexal, interstitial inflammatory lymphocytic infiltrate, which occasionally extends into the subcutaneous tissue . The depth of eosinophilic infiltration in the skin is associated with the type of clinical manifestations (papule, vesicle or panniculitis) . Flame figures were also found in the dermis of our patient as described by Qiao et al .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The characteristic histological feature is the presence of an eosinophil‐rich, perivascular and periadnexal, interstitial inflammatory lymphocytic infiltrate, which occasionally extends into the subcutaneous tissue . The depth of eosinophilic infiltration in the skin is associated with the type of clinical manifestations (papule, vesicle or panniculitis) . Flame figures were also found in the dermis of our patient as described by Qiao et al .…”
Section: Discussionsupporting
confidence: 76%
“…Eosinophilic dermatosis of hematological malignancy has been described in association with CLL in most of the cases, although it has also been reported with other B‐cell hematological malignancies (mantle cell lymphoma, acute lymphoblastic leukemia, large cell lymphoma, multiple myeloma), and with acute monocytic leukemia, myelofibrosis and mycosis fungoides . It is believed that in a patient with immunodeficiency due to hematological disease a trigger like insect bite, drug or virus induces cytokine production with an excess of interleukin‐4 and ‐5 and an altered immune response with predominance of eosinophils . The eruption occurs concurrent with or months to years after the onset of the hematological malignancy, but occasionally can precede the diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez‐Lojo et al . reported a case report where the skin eruption resolved when leukemia was controlled. We did not observe that in most of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature on insect-bite-like reaction in CLL consists of case reports (11)(12)(13)(14)(15)(16) and the largest series described until now included only 10 patients (6). The aim of the present study was to review the national experience with insect-bite-like reaction in a large group of patients with CLL, with emphasis on clinical and laboratory characteristics, management, and clinical outcome.…”
mentioning
confidence: 99%
“…Previous clinical studies have already revealed diverse patterns of local and systemic diseases, including arthropod bites, Wells’ syndrome presenting with eosinophilic cellulitis, immune complex vasculitis, atopy, erythema nodosum, hematologic disorders like refractory anemia with excess blasts, injection granuloma, streptococcal and other bacterial infections, toxocariasis, malignancies like B- and T-cell lymphoma, polyarteritis nodosa, eosinophilic fasciitis, eosinophilic folliculitis, hypereosinophilic syndrome, eosinophilic neuritis, chronic recurrent parotitis, nephrotic syndrome, glomerulonephritis, sarcoidosis, tuberculous pleurisy, larva migrans (gnathostomiasis), and psychiatric illnesses like drug dependency [2-4]. The skin lesions mostly vary from urticarial papules, plaques to purpura, pustules, and ulcerative lesions but always include a nodular subcutaneous component [1].…”
Section: Discussionmentioning
confidence: 99%